2015
DOI: 10.1155/2015/970730
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Adjunctive Treatments Added to Olanzapine or Clozapine for Weight Control in Patients with Schizophrenia: A Systematic Review and Meta‐Analysis

Abstract: Objectives. This study was conducted to review systematically adjunctive treatments for weight reduction in patients with schizophrenia and compare efficacies of clinical trials through meta-analysis, so as to provide effective clinical guideline regarding weight control for patients taking atypical antipsychotics. Methods. Candidate clinical trials were identified through searching the Cochrane Central Register of Controlled Trials, PubMed, and PsycINFO. Fourteen randomized clinical trials were included for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 30 publications
1
27
0
2
Order By: Relevance
“…By adding more evidence, our review found a more optimistic view of topiramate augmentation in attenuating psychotic symptoms than prior meta‐analyses in that effect size estimates were more robust with much more narrow 95% CIs throughout and in that effect sizes generalized to clozapine and non‐clozapine antipsychotics as well as across a number of other relevant design, patient, and illness variables. Furthermore, our meta‐analysis confirmed the benefits of topiramate augmentation for weight reduction/slowing of weight gain, consistent with the prior reviews and meta‐analyses . However, the prior reviews and meta‐analyses had been limited by the much smaller number of studies, fewer participants, and by the lack of inclusion of all the metabolic variables, ADRs, and non‐clozapine antipsychotics, as well as by a lack of quality/risk of bias assessment, and relevant subgroup and meta‐regression analyses.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…By adding more evidence, our review found a more optimistic view of topiramate augmentation in attenuating psychotic symptoms than prior meta‐analyses in that effect size estimates were more robust with much more narrow 95% CIs throughout and in that effect sizes generalized to clozapine and non‐clozapine antipsychotics as well as across a number of other relevant design, patient, and illness variables. Furthermore, our meta‐analysis confirmed the benefits of topiramate augmentation for weight reduction/slowing of weight gain, consistent with the prior reviews and meta‐analyses . However, the prior reviews and meta‐analyses had been limited by the much smaller number of studies, fewer participants, and by the lack of inclusion of all the metabolic variables, ADRs, and non‐clozapine antipsychotics, as well as by a lack of quality/risk of bias assessment, and relevant subgroup and meta‐regression analyses.…”
Section: Discussionsupporting
confidence: 83%
“…Topiramate's efficacy for improving psychopathology and/or reducing body weight in antipsychotic‐treated patients with schizophrenia has been explored in prior meta‐analyses , but the number of studies and their power were limited. Even the most recent and largest meta‐analysis included only 8 RCTs (6 reporting on efficacy and 7 reporting data on weight reduction).…”
Section: Introductionmentioning
confidence: 99%
“…To be sure, the recurrence or worsening of illness in some outpatients was completely due to non-compliance for the antipsychotic treatment during the trial, it was not associated with the concomitant use of topiramate or metformin although it was not consistent with Choi et al report. 33 As to topiramate on maintaining stability in schizophrenia or affective disorders, in this study, only three cases of psychiatric symptoms worsen were found in the topiramate and metformin group after the end of this study, no signi cant difference was found between the two groups. So, there is not enough evidence that topiramate might stabilize the illness of schizophrenia and affective disorders according to this results.…”
Section: Discussionmentioning
confidence: 48%
“…The efficacy of reboxetine in treating negative symptoms and/ or reducing AP-induced weight gain in schizophrenia have been examined in meta-analyses [10,12,[31][32][33][34]. Common limitations of these meta-analyses include the small number of included studies, resulting in insufficient power.…”
Section: Introductionmentioning
confidence: 99%
“…Common limitations of these meta-analyses include the small number of included studies, resulting in insufficient power. For example, 3 meta-analyses [12,33,34], each with 2 RCTs (n = 85) [18,22], found that reboxetine was superior to placebo in reducing AP-induced weight gain. Another meta-analysis [31] included 9 RCTs, but one of them was an open-label study [35], the inclusion of which violated standard recommendations [36].…”
Section: Introductionmentioning
confidence: 99%